新加坡英汉双语儿童汉语语法习得 = Singapore English-Chinese bilingual children's acquisition of Chinese grammar - 陈欣怡 Tan, Xin Yi (Nanyang Technological University, 2022)
语言迁移是双语习得的重要现象。新加坡儿童在早期阶段就开始同时输入至少两种不同的语言。然而，对于新加坡双语华族学习者来说，作为母语的华语实际上已成为次要语言，主要语言则由英语代替。因此，本研究希望考察新加坡双语儿童在汉语语法习得发展中受到英语干扰的程度。本研究主要分为两大部分：（1）通过问卷调查搜集受试者的个人与家庭背景等信息与（2）通过语言测试检测受试者的汉语语法掌握能力。结合问卷调查与语言测试所搜集的数据进行进一步的分析与讨论之后，本研究发现（1）新加坡双语儿童在汉语语法习得过程中，普遍受到英语的影响，但研究结果显示最显著的负迁移发生在汉语副词的语法掌握上；（2）语言因素与非语言因素在一定的程度上都将影响学习者的语言迁移。最后，本研究希望通过对新加坡双语儿童汉语语法习得现象的阐述，为双语习得研究与幼儿教学提供参考。Language transfer is an important phenomenon in bilingual acquisition. Singapore children are introduced to at least two different language simultaneously at an early stage. However, for Singapore bilingual Chinese learners, Chinese as a mother tongue has actually become a secondary language, with the primary language being replaced by English. Therefore, this study aims to examine the extent to which Singaporean bilingual children are influenced by English in their early development of Chinese grammar acquisition. The study is divided into two main parts: (1) a questionnaire to collect information about the subjects' personal and family backgrounds and (2) a language test to test the participants' grammatical acquisition of Chinese. After further analysis and discussion of the data collected through the questionnaires and language tests, it was found that (1) Singapore bilingual children were generally influenced by English in the acquisition of Chinese grammar, but the most significant negative transfer occurred in the grammatical acquisition of Chinese adverbs. (2) Both linguistic and non-linguistic factors influence learners' language transfer to a certain extent. Finally, it is hoped that this study will provide a reference for bilingual acquisition research and early childhood teaching by illustrating the phenomenon of Chinese grammar acquisition among Singapore bilingual children.